1996
DOI: 10.1021/es960348n
|View full text |Cite
|
Sign up to set email alerts
|

OH Radical Initiated Photooxidation of  2-Ethoxyethanol under Laboratory Conditions Related to the Troposphere:  Product Studies and Proposed Mechanism

Abstract: The products formed by the hydroxyl radical-initiated oxidation of 2-ethoxyethanol (CH 3 CH 2 OCH 2 CH 2 OH) have been investigated by irradiating synthetic air mixtures containing the substrate, methyl nitrite, and nitric oxide at ppm levels in a Teflon bag reactor at room temperature. The decay of reactants and the formation of products were monitored by gas chromatography and mass spectrometry. The major products ethyl formate [HC(O)OCH 2 CH 3 ], ethylene glycol monoformate [HC(O)OCH 2 CH 2 OH], ethylene gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 25 publications
3
30
1
Order By: Relevance
“…PF observation is consistent with previous studies of the hydroxyl reaction products of 2-ethoxyethyl acetate and ethyl 3-ethoxypropionate: the methylenes next to the ether oxygen are activated [4,5,10,11,21]. The PF product yield is larger than the trend expected using the data for 2-ethoxyethanol and 2-butoxyethanol that was reported by Stemmler et al [1,4]. A 43% ethyl formate yield was reported for 2-ethoxyethanol; a 35% butyl formate yield was reported for 2-butoxyethanol; while a 47% propyl formate yield was measured for 2-propoxyethanol [1,4].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…PF observation is consistent with previous studies of the hydroxyl reaction products of 2-ethoxyethyl acetate and ethyl 3-ethoxypropionate: the methylenes next to the ether oxygen are activated [4,5,10,11,21]. The PF product yield is larger than the trend expected using the data for 2-ethoxyethanol and 2-butoxyethanol that was reported by Stemmler et al [1,4]. A 43% ethyl formate yield was reported for 2-ethoxyethanol; a 35% butyl formate yield was reported for 2-butoxyethanol; while a 47% propyl formate yield was measured for 2-propoxyethanol [1,4].…”
Section: Discussionsupporting
confidence: 93%
“…From the mechanism proposed, PF is a product of hydrogen abstraction from methylene IV in the following structure: Using structure reactivity [12], a 39% propyl formate yield is expected. PF observation is consistent with previous studies of the hydroxyl reaction products of 2-ethoxyethyl acetate and ethyl 3-ethoxypropionate: the methylenes next to the ether oxygen are activated [4,5,10,11,21]. The PF product yield is larger than the trend expected using the data for 2-ethoxyethanol and 2-butoxyethanol that was reported by Stemmler et al [1,4].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…For the reactions of 2-butanol, the products observed were methyl ethyl ketone and acetaldehyde. Methyl [23] with the OH radical, also suggested that the reaction of the ␣-hydroxy alkyl radical with O 2 proceeds via hydrogen abstraction rather than O 2 addition. Consequently, the ␣-hydroxy radicals produced in the reactions of 1-propanol with H are expected to react with oxygen in a similar manner.…”
Section: Introductionmentioning
confidence: 99%